2022
DOI: 10.3390/children9020223
|View full text |Cite
|
Sign up to set email alerts
|

Maturation of Arousals during Day and Night in Preterm Infants

Abstract: The objective of this study was to compare the maturation of spontaneous arousals during day and night sleep in preterm and term infants. From the Autonomic Baby Evaluation study, the sleep and arousal characteristics of 12 preterm (35.1 ± 2.1 weeks’ gestational age, GA) and 21 term (39.8 ± 0.8 weeks GA) newborns were compared between diurnal and nocturnal sleep periods at birth (M0) and 6 months (M6) of age. Models were adjusted for time (night/day), maturation (M0/M6), prematurity (yes/no). We found that pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…In a previous issue of Children, Guyon et al, presented longitudinal data on the sleep structure and maturation of spontaneous arousals in a limited number of preterm and term infants from the Autonomic Baby evaluation study [1]. Participants were evaluated after birth in the maternity unit and at 6 months of age at home, using 24 h polysomnography (PSG).…”
Section: Introductionmentioning
confidence: 99%
“…In a previous issue of Children, Guyon et al, presented longitudinal data on the sleep structure and maturation of spontaneous arousals in a limited number of preterm and term infants from the Autonomic Baby evaluation study [1]. Participants were evaluated after birth in the maternity unit and at 6 months of age at home, using 24 h polysomnography (PSG).…”
Section: Introductionmentioning
confidence: 99%
“…The results varied due to the different GA of the enrolled cases, but most studies revealed that preterm infants experienced more total sleep time and AS, while less QS than term ones ( Anders and Keener, 1985 ; Ardura et al, 1995 ; Sahni et al, 1995 ; Hoppenbrouwers et al, 2005 ; Guyer et al, 2015 ; Georgoulas et al, 2021 ), which might reflect the accelerated neurological maturation of preterm infants ( Mirmiran et al, 2003a ; Bennet et al, 2018 ). Besides, preterm infants had fewer total arousals and, more specifically, fewer arousals in the AS ( Guyon et al, 2022 ), which seemed to cause a higher risk of sudden infant death syndrome ( Mirmiran et al, 2003a ; Bennet et al, 2018 ).…”
Section: The Characteristics Of Circadian Rhythms In Preterm Infantsmentioning
confidence: 99%
“…With developmental maturity, preterm infants have more sleep during nighttime but less during daytime ( Antonini et al, 2000 ; Korte et al, 2001 ; Guyer et al, 2015 ; Lan et al, 2019 ; Guyon et al, 2022 ). Meanwhile, as the PMA increased, the AS proportion comes out of a decreasing trend, but it is not true for the QS, IS, wakefulness, and activity, which all experience an increasing trend ( Anders and Keener, 1985 ; Curzi-Dascalova et al, 1988 ; Curzi-Dascalova et al, 1993 ; Borghese et al, 1995 ; Sahni et al, 1995 ; Ingersoll and Thoman, 1999 ; Mirmiran et al, 2003b ; Holditch-Davis et al, 2004 ; Hoppenbrouwers et al, 2005 ; Foreman et al, 2008 ; Dorn et al, 2014 ; Guyer et al, 2015 ; Lan et al, 2019 ; Cailleau et al, 2020 ; Park et al, 2020 ; Georgoulas et al, 2021 ; Guyon et al, 2022 ).…”
Section: The Characteristics Of Circadian Rhythms In Preterm Infantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to a group of age-matched control infants, these SIDS victims had significantly more subcortical activations during the first part of the night between 9:00 p.m. and midnight, and fewer cortical arousals during the latter part of the night, suggesting an incomplete arousal process ( 8 ). On the other hand, all known major risk factors for SIDS such as prone sleep position, in utero tobacco exposure, preterm births,… have been consistently associated with decrease in both spontaneous and induced arousals from sleep ( 9 11 ).…”
Section: Introductionmentioning
confidence: 99%